2011
DOI: 10.1007/s00213-011-2342-0
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol potentiates Δ9-tetrahydrocannabinol (THC) behavioural effects and alters THC pharmacokinetics during acute and chronic treatment in adolescent rats

Abstract: CBD can potentiate the psychoactive and physiological effects of THC in rats, most likely by delaying the metabolism and elimination of THC through an action on the CYP450 enzymes that metabolise both drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 56 publications
(94 reference statements)
14
128
1
1
Order By: Relevance
“…It must be noted that CBD's reversal of THC-induced laziness in slackers is a modest effect, an issue underscored by the small number (8 slackers) used. However, other studies have also shown that CBD-THC interactions produce only modest physiologic and psychological changes 36 that are sensitive to numerous factors, including the specific THC/CBD doses used, their ratio, and timing of coadministration. 37 Understanding the mechanism by which CBD partially ameliorates THC's effects may provide insight into why this effect is not as robust as expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that CBD's reversal of THC-induced laziness in slackers is a modest effect, an issue underscored by the small number (8 slackers) used. However, other studies have also shown that CBD-THC interactions produce only modest physiologic and psychological changes 36 that are sensitive to numerous factors, including the specific THC/CBD doses used, their ratio, and timing of coadministration. 37 Understanding the mechanism by which CBD partially ameliorates THC's effects may provide insight into why this effect is not as robust as expected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro evidence suggests that CBD may inhibit the effects of THC through negative allosteric modulation of the CB 1 receptor, 38 whereas human neuroimaging studies indicate that THC and CBD differentially influence brain activity while performing cognitive or emotional tasks. [39][40][41] And while both additive 36 and antagonistic 18,42 associations have been reported between these agents in rodents, to date no studies have provided a direct mechanism as to how CBD moderates THC's behavioural effects.…”
Section: Discussionmentioning
confidence: 99%
“…Findings to date suggest minimal CBD impact on apparent positive subjective effects induced by psychostimulants or THC [70,71,78]. Moreover, no animal studies have been published to date regarding CBD's effects on nicotine or alcohol.…”
Section: Cbd In Preclinical Addiction Modelsmentioning
confidence: 99%
“…CBD has also been shown to attenuate THC-induced memory impairment [80]. However, in mice and rats, CBD inhibits metabolism of THC, so that pretreatment with CBD can increase brain concentrations of THC and thereby potentiate its behavioral effects [82]. In a series of functional magnetic resonance imaging experiments in which CBD and THC were administered to healthy human subjects, the 2 compounds produced largely opposite patterns of activation during tasks involving memory, emotional processing, salience, and response inhibition in key brain regions implicated in schizophrenia, such as the striatum, prefrontal cortex, and hippocampus [3,81].…”
Section: Cbdmentioning
confidence: 99%